Recruitment during the period of Russian-Turkish war of 1735-1739 - Севастьянова І. (Видавничо-поліграфічний центр "Київський університет", 2007)
This article deals with the peculiarities of recruitment during the period of Russian-Turkish War of 1735-39.

Розкрито особливості рекрутських наборів у період російсько-турецької війни 1735–1739 рр.
Рекрутські набори під час російсько-турецької війни 1735–1739 років